Latent mean differences between men and women: The case of the Preference for the Intuition and Deliberation Scale - Cosentino, Alejandro César (2023)
Intuition and deliberation are two modes of thinking for decision making. The objective of this research was to compare latent means between men and women´s preference for intuition and deliberation. However, empirical studies on the Preference for Intuition and Deliberation scale (PID) measurement invariance were not available. The results of our study showed the original PID-based model did not show a good fit to the data. Nevertheless, a revised PID-based model showed strong and strict measurement invariance. As a result, latent mean comparison indicated that women showed more preference for intuition and less for deliberation than men.